Inovasi Gadjah Mada Bamboo Shelter (GAMBOOSTER) sebagai Smart and Eco Friendly Temporary Shelter bagi Korban Bencana - Utomo, Puji; Zein, Erwin Novian (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Various regions in Indonesia are often had a natural disaster. Ironically handling of post-disaster still seem indolent and not ready especially fullfill requirement of shelters. Orientation of the above problem, we have an innovations arise to make shelters with various of design concept, include : shelters that can harvest the rain water, earthquake resistant, eco friendly materials, get implementing smart technology system as a puzzle and implement the dynamic wall system. The main materials used in our innovation is bamboo with the economic, low cost and sustainable when it compared to wood or aother materials. Same with implementing of other building work, temporary shelter that we construct need standart tools equipment builders. This activity is divided in two types of work, thereâs fabrication site and construction site. On the implementation phase, we can starting from a literature search and discussion, survey tools and materials, permitting laboratories and make a shop drawing. After that, we can make the temporary shelters from the procurement of equipment and materials, work columns, beams, sloof, the walls and floor plate work, trust and roof work, finishing, construction phase and packaging. This product innovation is also equipped with a guide book for constructed, so our expectation is the temporary shelter can construct with effective and effisienly.Keyword : shelter, puzzle, bamboo, disaster